2023
DOI: 10.1111/jnc.15825
|View full text |Cite
|
Sign up to set email alerts
|

Functional imaging and neurochemistry identify in vivo neuroprotection mechanisms counteracting excitotoxicity and neurovascular changes in the hippocampus and visual cortex of obese and type 2 diabetic animal models

Abstract: Functional MRI (fMRI) with 1H‐MRS was combined on the hippocampus and visual cortex of animal models of obesity (high‐fat diet, HFD) and type 2 diabetes (T2D) to identify the involved mechanisms and temporal evolution of neurometabolic changes in these disorders that could serve as potentially reliable clinical biomarkers. HFD rats presented elevated levels of N‐acetylaspartylglutamate (NAAG) (p = 0.0365 vs. standard diet, SD) and glutathione (GSH) (p = 0.0494 vs. SD) in the hippocampus. NAAG and GSH levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…[1,6-13 C]-glucose infusion uncovers markedly diminished glutamate-glutamine cycling in the brain (encompassing hippocampus, thalamus, striatum, and part of the cortex), along with impaired glutamine synthesis and mitochondrial tricarboxylic acid metabolism, in Goto-Kakizaki versus control rats aged between 6 and 7 months (Girault et al, 2019). Elevated hippocampal glutamine was recorded in T2D HFD-STZ mice versus lean standard-diet fed controls aged 20 weeks following 10 weeks of diet, but no differences were seen in glutamate nor GABA (Caramelo et al, 2023).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…[1,6-13 C]-glucose infusion uncovers markedly diminished glutamate-glutamine cycling in the brain (encompassing hippocampus, thalamus, striatum, and part of the cortex), along with impaired glutamine synthesis and mitochondrial tricarboxylic acid metabolism, in Goto-Kakizaki versus control rats aged between 6 and 7 months (Girault et al, 2019). Elevated hippocampal glutamine was recorded in T2D HFD-STZ mice versus lean standard-diet fed controls aged 20 weeks following 10 weeks of diet, but no differences were seen in glutamate nor GABA (Caramelo et al, 2023).…”
Section: Discussionmentioning
confidence: 93%
“…Although there were few studies in the literature that detected elevated taurine in humans, this finding in the db/db mouse brain is much better characterized (Zheng et al, 2016;. A very recent study with a different HFD-STZ-induced T2D model reported elevated cortical taurine in T2D HFD mice compared to obese HFD mice (Caramelo et al, 2023). Brain taurine is also elevated in hyperglycemic STZ-induced T1D rats (Chandrasekaran et al, 2020;Duarte et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations